1994
DOI: 10.1021/jf00042a003
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Composition of Varietal Juices Produced from Fresh and Stored Apples

Abstract: Varietal juices were produced from 11 apple cultivara from three apple-growing regions of Ontario before and after cold storage in two consecutive crop years. Juices were analyzed for individual sugars using HPLC. The ranges of concentrations (grams per 100 mL) found for juice produced from fresh and stored fruit, respectively, were as follows: sucrose 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
36
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 30 publications
9
36
1
Order By: Relevance
“…Data presented in Table 3 illustrate the acids and sugars composition variability among red flesh, commercial and ancient apple cultivars. The GC pattern of acids and sugars composition is similar in all the examined cultivars and in accordance with literature (Wu et al 2007;Fuleki et al 1994).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Data presented in Table 3 illustrate the acids and sugars composition variability among red flesh, commercial and ancient apple cultivars. The GC pattern of acids and sugars composition is similar in all the examined cultivars and in accordance with literature (Wu et al 2007;Fuleki et al 1994).…”
Section: Resultssupporting
confidence: 91%
“…There were numerous studies examining apple sugar profiles (Fuleki et al 1994;Karadeniz, Ekşi 2002;Wu et al 2007). In agreement with these authors, fructose, sucrose and glucose were identified as the principal sugars.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Treatment 3 juices, the concentrations of all three sugars (fructose, glucose and sucrose) were significantly different from the control; fructose and glucose concentrations were much higher and sucrose concentration was lower in Treatment 3 compared with Treatment 1 (Tables 3 and 4). These changes in sugar concentrations of juices from stored apples were also observed by Fuleki et al, 29 who attributed the decrease in sucrose mainly to inversion of the sugar during storage, consequently increasing the glucose and fructose concentrations in the fruit. Some sugar may also have been lost through respiration during apple storage.…”
Section: Chemical Characteristicssupporting
confidence: 79%
“…High-performance liquid chromatography (HPLC) has become the method of choice for quantitative analysis of sugars in foods (Fuleki et al 1994 ;Camara et al 1996). Among all the quantitative chromatographic techniques for sugar analysis, HPLC is more attractive than gas chromatography (GC) since derivatives need not to be formed prior to analysis, and sample preparation time may therefore be reduced (Iverson and Bueno 1981 ;Shaw 1988 ;Ellianson 1996).…”
Section: Introductionmentioning
confidence: 99%